Nanotechnological basis for advanced sensors - Reithmaier, Johann Peter (Dordrecht, Netherlands Springer Dordrecht, 2011)
This book is based on the lectures and contributions of the NATO Advanced Study Institute on Nanotechnological Basis for Advanced Sensors held in Sozopol, Bulgaria, 30 May - 11 June, 2010. It gives a broad overview on this topic, and includes articles on: techniques for preparation and characterization of sensor materials; different types of nanoscaled materials for sensor applications, addressing both their structure (nanoparticles, nanocomposites, nanostructured films, etc.) and chemical nature (carbon-based, oxides, glasses, etc.); and on advanced sensors that exploit nanoscience and nanotechnology. In addition, the volume represents an interdisciplinary approach with authors coming from diverse fields such as physics, chemistry, engineering, materials science and biology. A particular strength of the book is its combination of longer papers, introducing the basic knowledge on a certain topic, and brief contributions highlighting special types of sensors and sensor material
Preface -- 1 Sensors and Nanotechnology -- Nanotechnology-Based Modern Sensors and Biosensors; W. Kulisch -- 2 Techniques for the Preparation of Sensor Materials -- Nonlinear Optical Sensors on Metal Nanoparticles Synthesized by Ion Implantation; A.L. Stepanov et al -- Laser Ablative Deposition of Polymer Films: A Promise for Sensor Fabrication; J. Blazevska-Gilev et al -- Fabrication of Porous and Dense Ceramics from Transitional Nano-Alumina; E. Fidancevska et al -- Modification of Nanosilica Surface by Methyl Methacrylate Silane Coupling Agents; I. Telegeev et al -- Microstructures Produced by Chemical Etching of Finely Scratched Silicon; E. Harea -- Multilayer Films and Capsules of Sodium Carboxymethylcellulose and Polyhexamethylenguanidine Hydrochloride; N. Guzenko et al -- Comparison of Photocatalytic Activity of TiO Anatase Prepared by the Sol-Gel Technique and Chemical Vapour Deposition on Naphtalene in the Gas Phase; G. Nacevski et al -- Ceramics for Advanced Sensors; R. Adziski et al -- 3 Techniques for the Characterization of Sensor Materials -- Surface Analytical Characterization of Biosensor Materials; G. Ceccone et al -- Nanovoids in Glasses and Polymers Probed by Positron Annihilation Lifetime Spectroscopy; T. Kavetskyy et al -- Detection of Structural Units of Nanocrystalline Diamond Surfaces Using Surface-Enhanced Raman Scattering; M. Veres et al -- 4 Sensor Materials -- 4.1 Carbon-Based Materials -- Production, Purification, Characterization, and Application of CNTs; A.T. Dimitrov et al -- 2D-Building Block for Functional Nanocomposites; C. Vallés et al -- PCL/MWCNT Nanocomposites as Nanosensors; A. Grozdanov et al -- 4.2 Oxide Materials -- Nanostructured ZnO Thin Films Properties and Applications; D. Dimova-Malinovska -- A Study of the Kinetics of the Electro-Chemical Deposition of Ce3/Ce Oxides ; I. Valov et al -- 4.3 Chalcogenide Glasses -- Multicomponent Chalcogenide Glasses Advanced Membrane Materials for Chemical Sensors and Nanosensors; S. Boycheva, V. Vassilev -- Optical Properties of Thin Ge-Se-In Chalcogenide Films for Sensor Applications; P. Petkov, E. Petkov -- Atomic Structure of (GE0.Se0.8)85B15 and (GE0.Se0.8)85In15 Glasses; I. Kaban et al -- Surface Development of (As2S3)1-x(AgI)x Thin Films for Gas Sensor Applications; K. Kolev et al -- Thin As-Se-Sb Films as Potential Medium for Optics and Sensor Application; V. Ilcheva et al -- Structure of AgI-AsSe Glasses by Raman Scattering and Ab Initio Calculations; O. Kostadinova et al -- Optical Properties of As-Based Chalcogenide Glasses; D. Harea et al -- IR Impurity Absorption in GeS2-In2S3AgI Chalcohalide Glasses; T. Kavetskyy et al -- New Chalcohalide Glasses from the GeSe2-Ag2Se-AgI System for Nanostructured Sensors; G. Vassilev et al -- 4.4 Further Glasses -- Thermally Induced Nanostructures in Samarium-Doped Glass Ceramics for X-Ray Sensor Applications ; D. Tonchev et al -- Synthesis and Phase Composition of Fe/Mn Containing Nanocrystals in Glasses from the System Na2O/MnO/SiO2/Fe2O3; R. Harizanova et al -- 4.5 Nanoparticles and other Nanostructures -- Nanostructured Materials in Different Dimensions for Sensing Applications; P. Morgen et al -- Field Enhancement in Plasmonic Gold Nanostructures on Templates of Anodized Aluminum for Sensor Applications; P. Nielsen et al -- Growth of SiC Nano-Whiskers on Powdered SiC; R. Dhiman, P. Morgen -- Tin Oxide Wiskers: Antimony Effect on Structure, Electrophysical, Optical and Sensor Properties; A.A. Zhukova et al -- Excimer Laser Preparation of SnO and SNO/TiO Nanoparticles -- Polymer Choleristic Liquid Crystal Flakes as New Candidates for Display and Sensor Applications; A. Trajkovska Petkoska -- Properties of Vanadium Bronzes Synthesized by Different Methods; A. Aleksandra et al -- 5 Sensors and Biosensors -- 5.1 Optical Sensors -- Semiconductor Lasers for Sensor Applications; C. Gilfert, J.P. Reithmaier -- Optical Characterization of Very Thin Films for Nanotechnological Basis of Sensors; P. Sharlandjiev -- Tellurium Thin Films in Sensor Technology; D. Tsiulyanu -- Yttrium Nanoparticle Hydrogen Gas Sensors; A.L. Stepanov et al -- Conductive Gas Sensors Prepared Using PLD; M. Jelínek et al -- Electrochemical Sensors for the Detection of Hydrogen Prepared by PLD and Sol-Gel Chemistry; G.A. Mousdis et al -- Acetone Sensing by Modified SnO Nanocrystalline Sensor Materials; V.V. Krivetsky et al -- Gas Sensor Based on Chalcohalide AgI-Containing Glasses; B. Monchev et al -- Photocatalytic Oxidation of Toluene on Modified TiO Nanoparticles; F. Jovi, V. Tomai -- Impedance Spectroscopy of Tellurium Thin Films Sensitive to NO; D. Tsiulyanu, O. Mocreac -- Piezoelectric Crystal Sensor for Ammonia Detection; T. Hristova-Vasileva et al -- 5.3 Biosensors -- Nanocrystalline Diamond Films for Biosensor Applications; C. Popov, W. Kulisch -- Surface Functionalization of Plasma Treated Ultrananocrystalline Diamond/Amorphous Carbon Composite Films; H. Koch et al -- Electrochemical Response of Biomolecules on Carbon Substrates: Comparison between Oxidized HOPG and O-Terminated Boron-Doped CVD Diamond; C. Baier et al -- Impact of Nanotopography and/or Functional Groups on Periodontal Ligament Cell Growth; H.T. Sasmazel et al -- Effect of ZnO Nanostructured Thin Films on Pseudomonas Putida Cell Division; I. Ivanova et al -- Comparison of Photocatalytic Activity of TiO Anatase Prepared by the Sol-Gel Technique and Chemical Vapour Deposition on Naphtalene in the Gas Phase; M. Marinkovski et al -- 5.4 Special Sensors -- Nanocomposite Sensors for Food Packaging; M. Avella et al -- Nanotechnologies and Nanosensors: Future Applications for the Conservation of Cultural Heritage; M. Avella et al -- Towards in situ-Process Control in Tribological or Tool Applications a Material Concept for the Design of Smart Thin Films Wear Sensors; S. Ulrich et al -- 5.5 Actuators -- Recent Developments and Challenges in Shape Memory Technology; M. Frotscher, G. Eggeler -- Micromachined Tunable Fabry-Pérot Filter Integrated into a Miniaturized Spectrometer for Low-Cost Applications; C. Woidt et al -- 6 Energy Economy Aspects -- Hydrogen Economy: The Role of Nano-Scaled Support Material for Electrocatalysts Aimed for Wataer Electrolysis; P. Paunovi et al -- Materials for Photovoltaic Applications; D. Dimova-Malinovska -- Subject Inde
Electronic reproduction.
Keywords: Detectors -- Congresses; Detectors -- Design and construction -- Congresses; Nanotechnology -- Congresses